2021
DOI: 10.3390/nano11040889
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Wearable Strain Sensor Based on MXene@Cotton Fabric with Network Structure

Abstract: Flexible and comfortable wearable electronics are as a second skin for humans as they can collect the physiology of humans and show great application in health and fitness monitoring. MXene Ti3C2Tx have been used in flexible electronic devices for their unique properties such as high conductivity, excellent mechanical performance, flexibility, and good hydrophilicity, but less research has focused on MXene-based cotton fabric strain sensors. In this work, a high-performance wearable strain sensor composed of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
(28 reference statements)
0
29
1
Order By: Relevance
“…It was found that the FePS 3 @rGO strain sensor resistance increased linearly with a corresponding gauge factor of 38.7 (R 2 = 0.96) at 40% strain. The obtained gauge factor value was superior to that previously reported for some of the 2D materials and carboncoated textile strain sensors [43][44][45][46] . The repeatability of the FePS 3 @rGO strain sensor was then examined using step and hold strain cycles, and the results are displayed in Supplementary Fig.…”
Section: Remotely Monitoring Physiological Parameterscontrasting
confidence: 73%
“…It was found that the FePS 3 @rGO strain sensor resistance increased linearly with a corresponding gauge factor of 38.7 (R 2 = 0.96) at 40% strain. The obtained gauge factor value was superior to that previously reported for some of the 2D materials and carboncoated textile strain sensors [43][44][45][46] . The repeatability of the FePS 3 @rGO strain sensor was then examined using step and hold strain cycles, and the results are displayed in Supplementary Fig.…”
Section: Remotely Monitoring Physiological Parameterscontrasting
confidence: 73%
“…fabricated a wearable high‐performance Ti 3 C 2 T x based strain sensor using the dip‐coating method and obtained a gauge factor of 4.11 at 3–15% of applied strain. [ 61 ] Uzun et al. fabricated highly conductive MXene coated cellulose yarns and utilized them as a strain sensor which displayed a gauge factor of 6.02% up to 20% of applied strain.…”
Section: Resultsmentioning
confidence: 99%
“…As a rechargeable secondary battery, LIBs have achieved great commercial success and are widely used in portable electronic products, electric vehicles, and the defense industry, etc., for their advantages of high operating voltage, high energy density, long cycle life, and environmental friendliness [175,230]. However, shortage of lithium resources can be a future problem.…”
Section: New Secondary Batterymentioning
confidence: 99%